If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(c-1/4)+(2c+3/6)=c-1
We move all terms to the left:
(c-1/4)+(2c+3/6)-(c-1)=0
We add all the numbers together, and all the variables
(+c-1/4)+(+2c+3/6)-(c-1)=0
We get rid of parentheses
c+2c-c+1-1/4+3/6=0
We calculate fractions
There is no solution for this equation
| c-1/4+2c+3/6=c-1 | | 8y-24+6y=4 | | 3y-7=3+4y+18 | | 6k=30 | | 13/15+4.71=x | | 5b-3b=7 | | 17x-28=12x+42 | | 18a^2+9a-20=0 | | 10x+2=14-6x | | (3x-60)=2 | | 5l/5=85/5 | | 7x-(-5x+19)=17 | | XxY=10 | | -(y-13/49)=-40 | | 24=2x-32 | | -8x+2(1x-5)=-10 | | 4b+75=983b= | | 3x-63=36 | | 3x-7(2x+9)=3 | | -4•3^6w=-1750 | | x+94=2x+29 | | 3x+29=2x | | -0.002*x+70=-0.004*x+90 | | x+19=3x-61 | | 2x+20°=60° | | _5x^_9x+13=0 | | 4*x=-8 | | (40+a)2/a2–(40/a)2=1 | | 5+x=2x-15 | | -3(8x+4)-2(3-23x)=3(4+7x) | | 12x-23=8x+9 | | 4x-5=6x-19 |